Comparision Of Molecular Typing Based On aflR Gene Polymorphism, aflR, Rapd And Microsatellite Typing Of Aspergillus Flavus Isolated From The Peanuts Collected In Tamil Nadu, India - GEORGE ROBIN.A.T,; S.KARTHICK RAJA NAMASHIVAYAM, (International Journal of Pharma and Bio Sciences, 2011)
Aflatoxins are potent carcinogenic compounds that occur naturally as secondary metabolites produced by some strains of Aspergillus flavus, Aspergillus parasiticus, Aspergillus nomics and Aspergillus tamarii. Aspergillus flavus is second to A. fumigatus as a cause of aspergillosis. In this basic study, we compared various molecular typing methods namely, restriction fragment length polymorphism (RFLP) analysis, random amplified polymorphic DNA analysis, analysis of the polymorphism of aflR gene by PCR-RFLP and microsatellite/oligonucleotide fingerprinting for A. flavus strains isolated from peanuts. A total of 20 strains and a standard strain were used for comparison. The typing methods were evaluated with respect to discriminatory power (D), reproducibility and typeability to determine their performance and utility. RAPD with primer R-108 produced nine types with a discriminatory power of 92.5, PCR-RFLP of aflR gene failed to discriminate those 20 isolates. The microsatellite fingerprinting with pms2 produced eight types with a discriminatory power of 93. Typeability was 100% in all methods. The reproducibility with repeated runs of the same DNA preparation or with different DNA preparation of the same strain was good for all the methods. RAPD and microsatellite finger printing were found to be useful methods for the molecular typing of A. flavus. A high degree of genetic variation was observed in the test population.